STRATEGI GURU DALAM MENGATASI KESULITAN SISWA MENGKONSTRUKSIKAN RESENSI CERITA PENDEK PADA PELAJARAN BAHASA INDONESIA KELAS XI SMKN 5 DENPASAR - Putu Dessy Fridayanthi; Ida Ayu Agung Ekasriadi (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Reviews are made in written form and are addressed to readers who review the weaknesses and strengths of a work. However, there are still students at school who cannot review short stories well. The purpose of this research is to determine students' difficulties in constructing short story reviews and to determine the implementation of teacher strategies in improving students' skills. The research subjects were class XI students at SMK Negeri 5 Denpasar for the 2023/2024 academic year. The data collection method in this research uses tests and observation. The data obtained was analyzed through quantitative descriptive. Data analysis is carried out on each data collected, both quantitative data and qualitative data. The research results showed that students' difficulties in aspects (1) suitability of the content of short story reviews were identified as slightly difficult with an average score of 63.46; (2) the grammar of short story reviews identified little difficulty with an average score of 65.76; (3) the short story reviewer's diction sentence structure was identified as slightly difficult with an average score of 65; (4) the coherent sentence structure of short story reviews identified little difficulty with an average score of 63.07; and (5) the formation of short story review paragraphs identified little difficulty with an average score of 65.76. The solution to overcome this teacher strategy is to improve classroom management by using pop up media.